(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2020)
The aim of this thesis is to find solutions that maximize the satisfaction of foreign tourists to service quality of Vietnamese tourism sector in the process of regional and international integration. Qualitative and quantitative research methods were combined to conduct 598 visitors with 48 observed variables to determine the factors affecting the satisfaction of foreign tourists to quality service of Vietnam tourism. The study results showed that 05 factor group is influenced (1) Responsiveness, (2) Competence, (3) Access, (4) Tangibles, and (5) Reliability. The results of this research are the basis of the recommendations proposed to increase the the satisfaction of foreign tourists to service quality of Vietnamese tourism sector in the near future.